Economic development in Tatarstan : global markets and a Russian region - McCann, Leo, 1976- (RoutledgeCurzon contemporary Russia and Eastern Europe series ;, 2005)
Based on extensive original research in Tatarstan, this book examines the economic development path followed by Tatarstan since the collapse of the Soviet Union.